2017
DOI: 10.1111/cas.13150
|View full text |Cite
|
Sign up to set email alerts
|

Increasing circulating exosomes‐carrying TRPC5 predicts chemoresistance in metastatic breast cancer patients

Abstract: Chemoresistance, the major obstacle in breast cancer chemotherapy, results in unnecessary chemotherapy and wasting of medical resources. No feasible method has been available to predict chemoresistance before chemotherapy. In our previous study, elevated expression of transient receptor potential channel TRPC5 was found to be an essential element for chemoresistance in breast cancer cells, and it was determined that it could be transferred to chemosensitive breast cancer cells through releasing extracellular v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(52 citation statements)
references
References 28 publications
0
45
0
Order By: Relevance
“…In vitro studies suggested a similar tendency by demonstrating a chemotherapy resistance transfer and neutralizing anti-HER2 treatment by EVs. [21][22][23][24]33 Post-NACT EV concentrations were associated with BC outcome of a reduced 3y-PFS and OS. Of note, the same cut-off value for EV concentrations post-NACT was obtained regarding 3y-PFS and OS for patient stratification.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In vitro studies suggested a similar tendency by demonstrating a chemotherapy resistance transfer and neutralizing anti-HER2 treatment by EVs. [21][22][23][24]33 Post-NACT EV concentrations were associated with BC outcome of a reduced 3y-PFS and OS. Of note, the same cut-off value for EV concentrations post-NACT was obtained regarding 3y-PFS and OS for patient stratification.…”
Section: Discussionmentioning
confidence: 95%
“…20 Further, BC-derived EVs can mediate drug resistance transfer from chemotherapy resistant BC cells to non-resistant BC cells via P-Glycoproteins or micro-RNAs. [21][22][23] Additionally, BC specific targeted drugs are reported to be neutralized by EVs expressing the drugs' target protein. 24 Clinical studies analyzing tumor-derived EVs associated biomarkers have been conducted for quite a few tumor entities.…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, there is a large amount of drug and chemoresistance proteins in the exosome. GSTP1, TGF-β1, TPRC5, and UCH-L1 are examples [97][98][99][100]. Finally, proteins that induce metastasis present highly in exosomes.…”
Section: Cell Ultracentrifugementioning
confidence: 99%
“…Drug and chemotherapy resistance [97] TGF-β1 Drug resistance [98] TPRC5 Chemotherapy resistance [99] UCH-L1 Chemotherapy resistance [100] Nephronectin Induce tumor mestasis [101] Caveolin-1 Enriched in metastasized cancer cell [36] Periostin Enriched in metastasized cancer cell [102] Myoferlin Enriched in metastasized cancer cell [31] Lung Cancer Mucin 5AC, B Lung cancer relapse and metastasis [103,104] Desmoglein-2 overspressed in non small cell lung cancer and induce cell growth [105] EGFR Oncogene in lung cancer [106,111,113,114] LRG1 Induce angiogenesis [108] Tim-3 Induce anti-tumor immune response [110] NY-SEO-1 Overexpressed in lung cancer [111] [111] EpCam Overexpressed in lung cancer [111] SGRN Overexpressed in lung cancer [112] TPM3 Overexpressed in lung cancer [112] THBS1 Overexpressed in lung cancer [112] HUWE1 Overexpressed in lung cancer [112] MUC 1 Overexpressed in lung cancer [112] Colon Cancer…”
Section: Gstp1mentioning
confidence: 99%
“…Initially deemed a mechanism of cellular waste disposal, extracellular vesicles (EVs) secreted by cells are now known to encapsulate a variety of biomolecules thought to be reflective of the cell from which they are released [1]. As such, they hold significant potential as circulating biomarkers of disease, with proposed applications in cancer diagnosis, prognostication, and prediction or monitoring of response to therapy [1][2][3][4][5][6][7]. However, rapid expansion in the field, as evidenced by a surge in publications, is not without challenges.…”
Section: Introductionmentioning
confidence: 99%